2022
DOI: 10.3389/fcell.2022.950927
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced signaling pathways to counteracting cardiac apoptotic processes

Abstract: Cardiovascular diseases are the most common cause of death in the world. One of the major causes of cardiac death is excessive apoptosis. However, multiple pathways through moderate exercise can reduce myocardial apoptosis. After moderate exercise, the expression of anti-apoptotic proteins such as IGF-1, IGF-1R, p-PI3K, p-Akt, ERK-1/2, SIRT3, PGC-1α, and Bcl-2 increases in the heart. While apoptotic proteins such as PTEN, PHLPP-1, GSK-3, JNK, P38MAPK, and FOXO are reduced in the heart. Exercise-induced mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 147 publications
(284 reference statements)
0
18
0
1
Order By: Relevance
“…Myostatin also inhibits the Akt/mTOR pathway and therefore suppresses skeletal protein synthesis and acts also through FOXO-1 and accelerates skeletal muscle atrophy. Myostatin is also a strong negative regulator for satellite cell activation [ 192 ]. According to the above mechanisms, myostatin is a negative regulator of skeletal muscle growth.…”
Section: Role Of Myokines In Non-diabetic Obesitymentioning
confidence: 99%
“…Myostatin also inhibits the Akt/mTOR pathway and therefore suppresses skeletal protein synthesis and acts also through FOXO-1 and accelerates skeletal muscle atrophy. Myostatin is also a strong negative regulator for satellite cell activation [ 192 ]. According to the above mechanisms, myostatin is a negative regulator of skeletal muscle growth.…”
Section: Role Of Myokines In Non-diabetic Obesitymentioning
confidence: 99%
“…The antioxidant and anti-apoptotic effects of regular physical activity in chronic diseases have been widely confirmed [ 16 , 17 ]. Accumulating studies have demonstrated that moderate exercise can inhibit HFD-induced testicular oxidative stress and apoptosis, and improve sperm quality and reproductive function [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-3 is a crucial mediator of apoptosis, and caspase-9 may trigger the mitochondrial apoptotic pathway. 34 Exposure to 50–400 μg/ml UCNP for 24 h significantly increased activated caspase-3 activity and protein levels in SGC-7901 cells in a concentration-dependent manner compared to controls ( p < 0.05), with the greatest increase seen in SGC-7901 cells exposed to 400 μg/ml UCNP ( p < 0.01). Exposure to 400 μg/ml UCNP for 24 h significantly increased activated caspase-9 activity and protein levels in SGC-7901 cells compared to control cells ( p < 0.05, Figure 4A–D).…”
Section: Resultsmentioning
confidence: 92%